2017
DOI: 10.1126/sciadv.1602935
|View full text |Cite
|
Sign up to set email alerts
|

First detection of equatorial dark dust lane in a protostellar disk at submillimeter wavelength

Abstract: An equatorial dark lane has been detected in the disk of a protostar in the earliest phase of star formation through ALMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 33 publications
(61 reference statements)
4
66
0
Order By: Relevance
“…1. The dusty disk scale height from Lee et al (2017b) is indicated in blue, the centrifugal barrier in red, and the COMs warm ring in orange (Lee et al 2017c;Bianchi et al 2017). …”
Section: Discussionmentioning
confidence: 99%
“…1. The dusty disk scale height from Lee et al (2017b) is indicated in blue, the centrifugal barrier in red, and the COMs warm ring in orange (Lee et al 2017c;Bianchi et al 2017). …”
Section: Discussionmentioning
confidence: 99%
“…In the case of HH212, the evidence comes from long-baseline ALMA continuum observation in Band 7 (0.85 mm) that resolved the disk vertical structure with a 0.02 resolution (Lee et al 2017). It reveals a dark lane near the disk midplane sandwiched between two brighter regions.…”
Section: Evolution Of Dust Settling In Edge-on Disks From Dust Imagingmentioning
confidence: 99%
“…02) resolution). Unfortunately, the disk is flared and optically thick 19 , preventing us from detecting the jet further in. The jet is highly collimated with a position angle measured to be ∼ 23…”
Section: ′′mentioning
confidence: 99%
“…The central source is the Class 0 protostar IRAS 05413-0104, with an estimated age of ∼ 40,000 yrs 18 . It has an accretion disk 19 and drives a powerful bipolar jet 20 . The jet, lying close (∼ 4 • ) to the plane of the sky 21 , is one of the best candidates to search for jet rotation.…”
Section: ′′mentioning
confidence: 99%
See 1 more Smart Citation